1994
DOI: 10.1139/x94-038
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation development in a hardwood-forest chronosequence in Nova Scotia

Abstract: Vegetation and aboveground biomass and nutrient capital (N, P, K, Ca, and Mg) were examined in a 22-stand, 75-year chronosequence within an angiosperm-dominated forest in Nova Scotia. Stands 20 years old and younger originated with clear-cutting, whereas older stands originated with wildfire. Early successional, ruderal species of vascular plants were prominent for ca. 5 years after clear-cutting, but they occurred as a part of a diverse, species-rich community dominated by more-tolerant species, many of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…Other studies have reported relatively high richness and diversity of ground vegetation during the initial stages of succession after timber harvesting, followed by a large decline as more shaded conditions develop (Shafi and Yarranton 1973;Bormann and Likens 1979;Hibbs 1983;Schoonmaker and McKee 1988;Burton 1989;Reiners 1992;Crowell and Freedman 1994;Gilliam et al 1995;Qi and Scarratt 1998;Roberts and Methven 1998). It has been suggested that the highest diversity of trees occurs in intermediate regenerative conditions, as this transitional period contains both early-and later-successional species (Loucks 1970;Auclair and Goff 1971;Pickett 1976;Connell 1978).…”
Section: Species Richness Density and Diversitymentioning
confidence: 96%
See 4 more Smart Citations
“…Other studies have reported relatively high richness and diversity of ground vegetation during the initial stages of succession after timber harvesting, followed by a large decline as more shaded conditions develop (Shafi and Yarranton 1973;Bormann and Likens 1979;Hibbs 1983;Schoonmaker and McKee 1988;Burton 1989;Reiners 1992;Crowell and Freedman 1994;Gilliam et al 1995;Qi and Scarratt 1998;Roberts and Methven 1998). It has been suggested that the highest diversity of trees occurs in intermediate regenerative conditions, as this transitional period contains both early-and later-successional species (Loucks 1970;Auclair and Goff 1971;Pickett 1976;Connell 1978).…”
Section: Species Richness Density and Diversitymentioning
confidence: 96%
“…The higher species richness and diversity in young plantations is due to their relatively open conditions and the spatial heterogeneity of environmental factors and vegetation (Shafi and Yarranton 1973;Crowell and Freedman 1994). Other studies have reported relatively high richness and diversity of ground vegetation during the initial stages of succession after timber harvesting, followed by a large decline as more shaded conditions develop (Shafi and Yarranton 1973;Bormann and Likens 1979;Hibbs 1983;Schoonmaker and McKee 1988;Burton 1989;Reiners 1992;Crowell and Freedman 1994;Gilliam et al 1995;Qi and Scarratt 1998;Roberts and Methven 1998).…”
Section: Species Richness Density and Diversitymentioning
confidence: 97%
See 3 more Smart Citations